Uma análise socioeconômica dos ingressantes do curso de bacharelado em química da Unesp/Ar durante o período de 1996-2018 - Scali, Tiago Junqueira [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This work aims to analyze the socioeconomic status of the student enrolled in the Bachelor of Chemistry course at the UNESP Institute of Chemistry in Araraquara from 1996 to 2018. In this sense, question 25 and question 9 were chosen from the socioeconomic questionnaire of the Vunesp aiming to carry out an analysis between the monthly family income, the place where the enrolled student attended high school (public or private school) over the years. A descriptive analysis of the data and the chi-square statistical test in Excel spreadsheets were used to verify associations and / or correlations between variables and groups. For data analysis, the answers to the questions were divided into groups according to the years of presidential terms to list and verify the educational policies of each period. In addition to interesting information about the socioeconomic status of chemistry students, our work can help the institution to better welcome students in the Bachelor of Chemistry course.

O presente trabalho tem como objetivo analisar a condição socioeconômico do aluno inscrito no curso de Bacharelado em Química do Instituto de Química da UNESP de Araraquara nos anos de 1996 a 2018. Nesse sentido, a questão 25 e a questão 9 foram escolhidas do questionário socioeconômico da Vunesp visando realizar uma análise entre a renda familiar mensal, o local onde o aluno inscrito realizou o Ensino Médio (escola pública ou particular) ao longo dos anos. Uma análise descritiva dos dados e o teste estatístico do qui-quadrado em planilhas do Excel foram utilizados para verificar associações e/ou correlações entre as variáveis e os grupos. Para a análise dos dados, as respostas das questões foram divididas em grupos de acordo com os anos de mandatos presidenciais para relacionar e verificar as políticas educacionais de cada período. Além de informações interessantes sobre a condição socioeconômica dos alunos de Química o nosso trabalho pode auxiliar a instituição em um melhor acolhimento dos alunos do curso de Bacharelado em Química.
A socio-economic analysis of entrants to the bachelor in chemistry course at Unesp/Ar during the period 1996-2018
Keywords: Química; Estatística; Condição socioeconômica; Unesp